2021
DOI: 10.1038/s41440-021-00752-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of febuxostat on left ventricular diastolic function in patients with asymptomatic hyperuricemia: a sub analysis of the PRIZE Study

Abstract: Hyperuricemia is related to an increased risk of cardiovascular events from a meta-analysis and antihyperuricemia agents may influence to cardiac function. We evaluated the effect of febuxostat on echocardiographic parameters of diastolic function in patients with asymptomatic hyperuricemia as a prespecified endpoint in the subanalysis of the PRIZE study. Patients in the PRIZE study were assigned randomly to either add-on febuxostat treatment group or control group with only appropriate lifestyle modification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The detailed study protocol and design are described in previous publications. [12][13][14][15][16] Briefly, patients with hyperuricemia (serum uric acid (SUA) level>7.0 mg/dL) and carotid plaques (maximum IMT of the common carotid artery≥1.1 mm) at screening were enrolled. Major exclusion criteria included uric acid lowering medications within 8 weeks prior to assessment of eligibility and gouty tophus or symptoms of gout arthritis within 1 year.…”
Section: Methods Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed study protocol and design are described in previous publications. [12][13][14][15][16] Briefly, patients with hyperuricemia (serum uric acid (SUA) level>7.0 mg/dL) and carotid plaques (maximum IMT of the common carotid artery≥1.1 mm) at screening were enrolled. Major exclusion criteria included uric acid lowering medications within 8 weeks prior to assessment of eligibility and gouty tophus or symptoms of gout arthritis within 1 year.…”
Section: Methods Study Design and Participantsmentioning
confidence: 99%
“…This is a subanalysis of the PRIZE Study, a multicentre, prospective, randomised, open-label, blinded-endpoint trial to assess a hypothesis if febuxostat delays carotid intima–media thickness (IMT) progression in patients with hyperuricemia. The detailed study protocol and design are described in previous publications 12–16. Briefly, patients with hyperuricemia (serum uric acid (SUA) level>7.0 mg/dL) and carotid plaques (maximum IMT of the common carotid artery≥1.1 mm) at screening were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“… 64 Nonetheless, further sub-analysis showed that the use of febuxostat was associated with better diastolic function and decreased arterial stiffness. 60 , 65 , 66 …”
Section: Cardiovascular Effect Of Urate Lowering Agentsmentioning
confidence: 99%
“…Furuhashi et al reported that plasma xanthine oxidoreductase (XOR) activity was associated with hypertension in 271 nondiabetic subjects in the Tanno–Sobetsu Study [ 192 ]. Kusunose et al reported that additional febuxostat treatment in patients with asymptomatic hyperuricemia for 24 months might have potential prevention effects on impaired diastolic dysfunction in the subanalysis of the PRIZE study [ 193 ]. These reports suggested the potential direct antioxidant effects of the treatment as reflected in serum uric acid levels as well as its xanthine-oxidase-lowering properties in tissue [Supplementary Information 11 - 3 ].…”
Section: Hot Topics In Uric Acid Research: the Difficulties Of Managi...mentioning
confidence: 99%